Evaluation of Serratus Anterior Plane Block for Pain Relief in Patients Undergoing MIDCAB Surgery. Issue 2 (March 2020) - Gautam, Sujeet; Pande, Shantanu; Agarwal, Anil; Agarwal, S. K.; Rastogi, Amit; Shamshery, Chetna; Singh, Ankita
Objective: The minimally invasive direct coronary artery bypass (MIDCAB) surgery is associated with severe chest pain in the first 2 to 3 postoperative days; this may delay the patient recovery. In this randomized controlled trial we evaluated the role of serratus anterior plane (SAP) block for postoperative pain relief in patients undergoing MIDCAB surgery. Methods: Patients undergoing MIDCAB surgery were randomized into 2 groups of 25 each; SAP group received 20 mL of 0.2% ropivacaine with 1 μg/mL fentanyl as bolus followed by infusion at 8 mL/h; control group received saline for both bolus and infusion. Primary outcome measure was postoperative pain when supine, and during deep inspiration, coughing, and patient movement; secondary outcome measures were requirement of postoperative intravenous fentanyl and opioid-related side effects. All patients were followed at 6-hourly intervals for 48 hours in the postoperative period. Results were analyzed by the Student's t -test, χ 2 test, Mann–Whitney U -test and Kruskall–Wallis test. A P -value <0.05 was considered significant. Results: The 2 groups were similar with respect to patient characteristics. Static and dynamic pain visual analog scale scores were significantly reduced in the SAP group as compared to the control group at most of the time points of assessment ( P < 0.05). Patient-controlled fentanyl requirements were reduced in the SAP group as compared to control group on the second postoperative day ( P < 0.05). Conclusions: SAP block reduced the postoperative pain scores and opioid requirements in patients undergoing MIDCAB surgery.